Individual Differences in Print Exposure Predict Use of Implicit Causality in Pronoun Comprehension and Referential Prediction - Johnson, Elyce; Arnold, Jennifer E. (Frontiers in Psychology, 2021)
In three experiments we measured individual patterns of pronoun comprehension (Exps. 1 & 2) and referential prediction (Exp. 3) in implicit causality contexts and compared these with a measure of participants’ print exposure (Author Recognition Task; ART). Across all three experiments, we found that ART interacted with verb bias, such that participants with higher scores demonstrated a stronger semantic bias, i.e. they tended to select the pronoun or predict the re-mention of the character that was congruent with an implicit cause interpretation. This suggests that print exposure changes the way language is processed at the discourse level, and in particular, that it is related to implicit cause sensitivity.